Analisis Kendala Sisi Darat (landside) oleh Petugas Pelayanan Terminal (Terminal Service Officer) Di PT. Angkasa Pura I Bandar Udara Internasional Zainuddin Abdul Madjid Lombok Nusa Tenggara Barat - Ilham Ramadhan; Eny Sri Haryati (Student Research Journal, 2023)
The Airport Operation Terminal and Landside Unit is a unit that provides services to airport users through its division, better known as the Terminal Service Officer (TSO), providing services to airport service users in the terminal and Landside areas. This study aims to explain what are the obstacles and what are the solutions for TSO officers in solving the obstacles. This study uses primary and secondary data. The subjects in this research are Terminal Service Officers. Data collection methods used are observation, interviews and documentation. The location of this research was carried out at PT. Angkasa Pura I Zainuddin Abdul Madjid International Airport Lombok West Nusa Tenggara with a placement in the Terminal Service Officer (TSO). This data analysis uses qualitative data. The results of this research regarding the Terminal Service Officer are the lack of cleaning service officers in maintaining the cleanliness of the facility, the lack of trolleyman officers in supplying the availability of trolleys and the lack of assertiveness of Aviation Security officers in giving warnings to street vendors and passenger escorts. While the solutions for Terminal Service Officer personnel in resolving problems are in accordance with the applicable Standard Operating Procedures. The solutions that are not listed in the Standard Operating Procedures are initiatives from Terminal Service Officer personnel who are none other than to provide maximum service to airport service users.